Fuzzy control enerygy efficient hybrid engine for small scale vehicle - Rahman, Mohammed Ataur; Hossain, Altab; Rashid, Muhammad Mahbubur (Maxwell Scientific Organization, 2013)
This study describes a fuel efficient and low emission cost effective hybrid engine for small scale vehicle. The main focus of this study is to downsize engine and improve the fuel consumption and reduce the emission. The proposed engine has been developed with integrating a 4 stroke 70 cc engines, a 12 volt generator, two supercapacitors of 2 Farad and a 12 volt DC battery for operating a 2.26 kN vehicle in the speed range of 30-45 km/h. It is estimated that the DC motor needs power in the range of 360-400 watt to propel the car with speed of 35-45 km/h. Test result shows that the hybrid engine able to produce the desired power for propelling the car with speed of 35-45 km/h. A vehicle of 2.26 kN including 0.69 kN driver’s weight was tested by using 100 ml fuel both in laboratory and road experiment. It was found that the vehicle has travelled 84.225 km for equivalent of 1 L fuel without any problem of the proposed engine. But the engine was stuck at the speed of 7000 rpm which was mainly due to the safety features in the rectification circuit which cut off the current supply for exceeding the predetermine current of 70A at 7000 rpm.